The Mediating Roles of Consumer Satisfaction and Word-of-Mouth in the Relationship between Service Quality, Price Fairness, and Loyalty in Indonesian Fast Food - Hadi, Seno Sudarmono; Wiryawan, Nizam Jim; Darmansah, Darmansah (International Review of Management and Marketing, 2026)
This study aims to analyze the influence of service quality and price fairness on consumer loyalty in the fast-food restaurant industry in Tangerang, Indonesia. It further investigates the mediating roles of consumer satisfaction and word-of-mouth communication (WOM) in these relationships. A quantitative research approach was employed using Structural Equation Modeling (SEM) with LISREL software to test the proposed relationships. Data were collected from 347 respondents who visited six fast-food restaurants in Tangerang, including both local and international franchises. The stratified random sampling technique was used to ensure representativeness. The results indicate that service quality positively influences consumer satisfaction (loading factor: 0.64, t-value: 2.44) and WOM (loading factor: 0.36, t-value: 6.00). However, service quality negatively affects consumer loyalty (loading factor: -0.21, t-value: 3.25). Price fairness does not significantly impact consumer satisfaction (loading factor: 0.00, t-value: 0.065) but has a positive effect on WOM (loading factor: 0.36, t-value: 8.12) and consumer loyalty (loading factor: 0.39, t-value: 9.13). Moreover, consumer satisfaction does not significantly influence WOM (loading factor: -0.33, t-value: 0.55) but has a moderate positive effect on consumer loyalty (loading factor: 0.23, t-value: 3.64). The strongest relationship is found between consumer loyalty and WOM (loading factor: 0.65, t-value: 13.31), indicating that loyal customers are more likely to share positive experiences. Fast-food restaurant managers should focus on enhancing service quality to boost customer satisfaction and encourage positive WOM communication. Although price fairness is crucial, it plays a greater role in fostering WOM and loyalty rather than directly influencing satisfaction. The findings suggest that strategic service quality improvements, fair pricing policies, and WOM-driven marketing approaches are essential for sustaining customer engagement and competitive advantage. This study provides empirical evidence on the complex interplay between service quality, price fairness, consumer satisfaction, and loyalty in Indonesia’s fast-food industry.